Carto-fiction: narrativising maps through creative writing. (13th October 2019) - Peterle, Giada
Abstract: This study reacts to the recent call for a narrativisation of maps' life in post-representational cartography, proposing 'cartographic fictional writing' as a means to move geography's 'creative (re)turn' from a place-centred to a 'carto-centred' perspective, and as an epistemological tool to go on rethinking maps from post-representational perspectives. First, 'carto-fiction' is defined as a self-reflexive (autoethnographic), ethnofictional, creative carto-centred product/practice of research. Second, by including the entire short story entitled 'Unfolding Berlin' and an autoethnographic account on how it emerged, this study strives to both theorise and perform carto-fictional writing as an embodied and trans-subjective mapping experience. My goal is to propose 'carto-fiction' as a prolific tool to let emotional, subjective cartographies emerge and to narrativise maps as mapping practices. The article further strives to focus on the mapping power of creative writing, and carto-fictional writing and reading will be interpreted as mapping performances, in which subjects are bodily and emotionally engaged. The inclusion of original illustrations aims to involve readers in a visual experience and to further stimulate their spatial imagination: each reader is asked to reflect on his/her own mapping experiences to interpret the fictional story and, thus, the paper itself attempts to unfold unpredicted creative cartographic practices.